2021
DOI: 10.3389/fnmol.2021.666673
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Relationship Between Calcium Signaling and Circadian Clocks: Implications for Calcium Homeostasis, Clock Function, and Therapeutics

Abstract: Graphical AbstractReciprocal relationship between Ca2+ signaling and the circadian clock. In Drosophila and mice, circadian clocks impose a daily rhythmicity to Ca2+ signaling; and, conversely, Ca2+ rhythms and signaling contribute to transmitting daily external signals to the clock TTFL. This bidirectional regulation is critical to the daily rhythmicity of many physiological and behavioral processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 113 publications
0
13
0
Order By: Relevance
“…Our data show a significant and substantial decrease in transcript levels of multiple phototransduction genes, and we propose that the cumulative decrease in expression of their corresponding proteins causes the light-dependent retinal degeneration in flies expressing Clk DN . However, because disrupting Clk:Cyc activity in photoreceptors had widespread effects on gene expression and chromatin accessibility, we cannot exclude the possibility that other pathways such as autophagy [77], Ca 2+ signaling [78] and phosphoinositide metabolism [79] also contribute to the onset of light-dependent retinal degeneration.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…Our data show a significant and substantial decrease in transcript levels of multiple phototransduction genes, and we propose that the cumulative decrease in expression of their corresponding proteins causes the light-dependent retinal degeneration in flies expressing Clk DN . However, because disrupting Clk:Cyc activity in photoreceptors had widespread effects on gene expression and chromatin accessibility, we cannot exclude the possibility that other pathways such as autophagy [77], Ca 2+ signaling [78] and phosphoinositide metabolism [79] also contribute to the onset of light-dependent retinal degeneration.…”
Section: Plos Geneticsmentioning
confidence: 99%
“…In humans, MICU3 is a brain-specific isoform of the mitochondrial calcium uniporter subunit particularly expressed in astrocytes, thus suggesting that a dysregulated mitochondrial calcium uptake in astrocytes contributes to PD progression [ 42 ]. It is not surprising, though, that knockdown of a gene like MICU3 results in altered behavioural locomotion, as calcium signalling is central for regulating circadian behaviour [ 43 ]. CtsB1 and CG33181 knockdown lines displayed normal climbing ability at day 5 and exacerbate climbing ability at days 10 and 15 ( Figure 3 and Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, UCP1 gene expression is regulated by the clock gene Reverbα and, therefore, exhibits circadian rhythmicity in BAT ( 23 ). In addition, many genes encoding proteins involved in Ca 2+ signaling are circadianly expressed in the skeletal muscle, and at least a subset of them, including the SERCA gene, may be regulated by the core clock component CLOCK-BMAL1 ( 24 , 25 ). Furthermore, we have shown that mice with brown adipocyte-specific Bmal1 KO show reduced thermogenesis despite the elevated expression of UCP1, probably due to impaired fatty acid utilization in BAT ( 13 ).…”
Section: Discussionmentioning
confidence: 99%